-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathZOL.agda
292 lines (234 loc) · 11.2 KB
/
ZOL.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
{-# OPTIONS --prop --rewriting #-}
module ZOL (PV : Set) where
open import PropUtil
open import ListUtil
data Form : Set where
Var : PV → Form
_⇒_ : Form → Form → Form
_∧∧_ : Form → Form → Form
⊤⊤ : Form
infixr 10 _∧∧_
infixr 8 _⇒_
{- Contexts -}
Con = List Form
private
variable
A : Form
A' : Form
B : Form
B' : Form
C : Form
F : Form
G : Form
Γ : Con
Γ' : Con
Γ'' : Con
x : PV
{--- DEFINITION OF ⊢ ---}
data _⊢_ : Con → Form → Prop where
zero : A ∈ Γ → Γ ⊢ A
lam : (A ∷ Γ) ⊢ B → Γ ⊢ (A ⇒ B)
app : Γ ⊢ (A ⇒ B) → Γ ⊢ A → Γ ⊢ B
andi : Γ ⊢ A → Γ ⊢ B → Γ ⊢ A ∧∧ B
ande₁ : Γ ⊢ A ∧∧ B → Γ ⊢ A
ande₂ : Γ ⊢ A ∧∧ B → Γ ⊢ B
true : Γ ⊢ ⊤⊤
infix 5 _⊢_
zero⊢ : (A ∷ Γ) ⊢ A
zero⊢ = zero zero∈
one⊢ : (B ∷ A ∷ Γ) ⊢ A
one⊢ = zero (next∈ zero∈)
-- We can add hypotheses to a proof
addhyp⊢ : Γ ∈* Γ' → Γ ⊢ A → Γ' ⊢ A
addhyp⊢ s (zero x) = zero (mon∈∈* x s)
addhyp⊢ s (lam h) = lam (addhyp⊢ (both∈* s) h)
addhyp⊢ s (app h h₁) = app (addhyp⊢ s h) (addhyp⊢ s h₁)
addhyp⊢ s (andi h₁ h₂) = andi (addhyp⊢ s h₁) (addhyp⊢ s h₂)
addhyp⊢ s (ande₁ h) = ande₁ (addhyp⊢ s h)
addhyp⊢ s (ande₂ h) = ande₂ (addhyp⊢ s h)
addhyp⊢ s (true) = true
-- Extension of ⊢ to contexts
_⊢⁺_ : Con → Con → Prop
Γ ⊢⁺ [] = ⊤
Γ ⊢⁺ (F ∷ Γ') = (Γ ⊢ F) ∧ (Γ ⊢⁺ Γ')
infix 5 _⊢⁺_
-- We show that the relation respects ∈*
mon∈*⊢⁺ : Γ' ∈* Γ → Γ ⊢⁺ Γ'
mon∈*⊢⁺ zero∈* = tt
mon∈*⊢⁺ (next∈* x h) = ⟨ (zero x) , (mon∈*⊢⁺ h) ⟩
-- The relation respects ⊆
mon⊆⊢⁺ : Γ' ⊆ Γ → Γ ⊢⁺ Γ'
mon⊆⊢⁺ h = mon∈*⊢⁺ (⊆→∈* h)
-- The relation is reflexive
refl⊢⁺ : Γ ⊢⁺ Γ
refl⊢⁺ {[]} = tt
refl⊢⁺ {x ∷ Γ} = ⟨ zero⊢ , mon⊆⊢⁺ (next⊆ zero⊆) ⟩
-- We can add hypotheses to to a proof
addhyp⊢⁺ : Γ ∈* Γ' → Γ ⊢⁺ Γ'' → Γ' ⊢⁺ Γ''
addhyp⊢⁺ {Γ'' = []} s h = tt
addhyp⊢⁺ {Γ'' = x ∷ Γ''} s ⟨ Γx , ΓΓ'' ⟩ = ⟨ addhyp⊢ s Γx , addhyp⊢⁺ s ΓΓ'' ⟩
-- The relation respects ⊢
halftran⊢⁺ : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁺ Γ' → Γ' ⊢ F → Γ ⊢ F
halftran⊢⁺ {Γ' = F ∷ Γ'} h⁺ (zero zero∈) = proj₁ h⁺
halftran⊢⁺ {Γ' = F ∷ Γ'} h⁺ (zero (next∈ x)) = halftran⊢⁺ (proj₂ h⁺) (zero x)
halftran⊢⁺ h⁺ (lam h) = lam (halftran⊢⁺ ⟨ (zero zero∈) , (addhyp⊢⁺ (right∈* refl∈*) h⁺) ⟩ h)
halftran⊢⁺ h⁺ (app h h₁) = app (halftran⊢⁺ h⁺ h) (halftran⊢⁺ h⁺ h₁)
halftran⊢⁺ h⁺ (andi hf hg) = andi (halftran⊢⁺ h⁺ hf) (halftran⊢⁺ h⁺ hg)
halftran⊢⁺ h⁺ (ande₁ hfg) = ande₁ (halftran⊢⁺ h⁺ hfg)
halftran⊢⁺ h⁺ (ande₂ hfg) = ande₂ (halftran⊢⁺ h⁺ hfg)
halftran⊢⁺ h⁺ (true) = true
-- The relation is transitive
tran⊢⁺ : {Γ Γ' Γ'' : Con} → Γ ⊢⁺ Γ' → Γ' ⊢⁺ Γ'' → Γ ⊢⁺ Γ''
tran⊢⁺ {Γ'' = []} h h' = tt
tran⊢⁺ {Γ'' = x ∷ Γ*} h h' = ⟨ halftran⊢⁺ h (proj₁ h') , tran⊢⁺ h (proj₂ h') ⟩
{--- DEFINITIONS OF ⊢⁰ and ⊢* ---}
-- ⊢⁰ are neutral forms
-- ⊢* are normal forms
mutual
data _⊢⁰_ : Con → Form → Prop where
zero : A ∈ Γ → Γ ⊢⁰ A
app : Γ ⊢⁰ (A ⇒ B) → Γ ⊢* A → Γ ⊢⁰ B
ande₁ : Γ ⊢⁰ A ∧∧ B → Γ ⊢⁰ A
ande₂ : Γ ⊢⁰ A ∧∧ B → Γ ⊢⁰ B
data _⊢*_ : Con → Form → Prop where
neu⁰ : Γ ⊢⁰ Var x → Γ ⊢* Var x
lam : (A ∷ Γ) ⊢* B → Γ ⊢* (A ⇒ B)
andi : Γ ⊢* A → Γ ⊢* B → Γ ⊢* (A ∧∧ B)
true : Γ ⊢* ⊤⊤
infix 5 _⊢⁰_
infix 5 _⊢*_
-- Both are tighter than ⊢
⊢⁰→⊢ : Γ ⊢⁰ F → Γ ⊢ F
⊢*→⊢ : Γ ⊢* F → Γ ⊢ F
⊢⁰→⊢ (zero h) = zero h
⊢⁰→⊢ (app h x) = app (⊢⁰→⊢ h) (⊢*→⊢ x)
⊢⁰→⊢ (ande₁ h) = ande₁ (⊢⁰→⊢ h)
⊢⁰→⊢ (ande₂ h) = ande₂ (⊢⁰→⊢ h)
⊢*→⊢ (neu⁰ x) = ⊢⁰→⊢ x
⊢*→⊢ (lam h) = lam (⊢*→⊢ h)
⊢*→⊢ (andi h₁ h₂) = andi (⊢*→⊢ h₁) (⊢*→⊢ h₂)
⊢*→⊢ true = true
-- We can add hypotheses to a proof
addhyp⊢⁰ : Γ ∈* Γ' → Γ ⊢⁰ A → Γ' ⊢⁰ A
addhyp⊢* : Γ ∈* Γ' → Γ ⊢* A → Γ' ⊢* A
addhyp⊢⁰ s (zero x) = zero (mon∈∈* x s)
addhyp⊢⁰ s (app h h₁) = app (addhyp⊢⁰ s h) (addhyp⊢* s h₁)
addhyp⊢⁰ s (ande₁ h) = ande₁ (addhyp⊢⁰ s h)
addhyp⊢⁰ s (ande₂ h) = ande₂ (addhyp⊢⁰ s h)
addhyp⊢* s (neu⁰ x) = neu⁰ (addhyp⊢⁰ s x)
addhyp⊢* s (lam h) = lam (addhyp⊢* (both∈* s) h)
addhyp⊢* s (andi h₁ h₂) = andi (addhyp⊢* s h₁) (addhyp⊢* s h₂)
addhyp⊢* s true = true
-- Extension of ⊢⁰ to contexts
-- i.e. there is a neutral proof for any element
_⊢⁰⁺_ : Con → Con → Prop
Γ ⊢⁰⁺ [] = ⊤
Γ ⊢⁰⁺ (F ∷ Γ') = (Γ ⊢⁰ F) ∧ (Γ ⊢⁰⁺ Γ')
infix 5 _⊢⁰⁺_
-- The relation respects ∈*
mon∈*⊢⁰⁺ : Γ' ∈* Γ → Γ ⊢⁰⁺ Γ'
mon∈*⊢⁰⁺ zero∈* = tt
mon∈*⊢⁰⁺ (next∈* x h) = ⟨ (zero x) , (mon∈*⊢⁰⁺ h) ⟩
-- The relation respects ⊆
mon⊆⊢⁰⁺ : Γ' ⊆ Γ → Γ ⊢⁰⁺ Γ'
mon⊆⊢⁰⁺ h = mon∈*⊢⁰⁺ (⊆→∈* h)
-- This relation is reflexive
refl⊢⁰⁺ : Γ ⊢⁰⁺ Γ
refl⊢⁰⁺ {[]} = tt
refl⊢⁰⁺ {x ∷ Γ} = ⟨ zero zero∈ , mon⊆⊢⁰⁺ (next⊆ zero⊆) ⟩
-- A useful lemma, that we can add hypotheses
addhyp⊢⁰⁺ : Γ ∈* Γ' → Γ ⊢⁰⁺ Γ'' → Γ' ⊢⁰⁺ Γ''
addhyp⊢⁰⁺ {Γ'' = []} s h = tt
addhyp⊢⁰⁺ {Γ'' = A ∷ Γ'} s ⟨ Γx , ΓΓ'' ⟩ = ⟨ addhyp⊢⁰ s Γx , addhyp⊢⁰⁺ s ΓΓ'' ⟩
-- The relation preserves ⊢⁰ and ⊢*
halftran⊢⁰⁺* : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁰⁺ Γ' → Γ' ⊢* F → Γ ⊢* F
halftran⊢⁰⁺⁰ : {Γ Γ' : Con} → {F : Form} → Γ ⊢⁰⁺ Γ' → Γ' ⊢⁰ F → Γ ⊢⁰ F
halftran⊢⁰⁺* h⁺ (neu⁰ x) = neu⁰ (halftran⊢⁰⁺⁰ h⁺ x)
halftran⊢⁰⁺* h⁺ (lam h) = lam (halftran⊢⁰⁺* ⟨ zero zero∈ , addhyp⊢⁰⁺ (right∈* refl∈*) h⁺ ⟩ h)
halftran⊢⁰⁺* h⁺ (andi h₁ h₂) = andi (halftran⊢⁰⁺* h⁺ h₁) (halftran⊢⁰⁺* h⁺ h₂)
halftran⊢⁰⁺* h⁺ true = true
halftran⊢⁰⁺⁰ {Γ' = x ∷ Γ'} h⁺ (zero zero∈) = proj₁ h⁺
halftran⊢⁰⁺⁰ {Γ' = x ∷ Γ'} h⁺ (zero (next∈ h)) = halftran⊢⁰⁺⁰ (proj₂ h⁺) (zero h)
halftran⊢⁰⁺⁰ h⁺ (app h h') = app (halftran⊢⁰⁺⁰ h⁺ h) (halftran⊢⁰⁺* h⁺ h')
halftran⊢⁰⁺⁰ h⁺ (ande₁ h) = ande₁ (halftran⊢⁰⁺⁰ h⁺ h)
halftran⊢⁰⁺⁰ h⁺ (ande₂ h) = ande₂ (halftran⊢⁰⁺⁰ h⁺ h)
-- The relation is transitive
tran⊢⁰⁺ : {Γ Γ' Γ'' : Con} → Γ ⊢⁰⁺ Γ' → Γ' ⊢⁰⁺ Γ'' → Γ ⊢⁰⁺ Γ''
tran⊢⁰⁺ {Γ'' = []} h h' = tt
tran⊢⁰⁺ {Γ'' = x ∷ Γ} h h' = ⟨ halftran⊢⁰⁺⁰ h (proj₁ h') , tran⊢⁰⁺ h (proj₂ h') ⟩
{--- Simple translation with in an Environment ---}
Env = PV → Prop
⟦_⟧ᶠ : Form → Env → Prop
⟦ Var x ⟧ᶠ ρ = ρ x
⟦ A ⇒ B ⟧ᶠ ρ = (⟦ A ⟧ᶠ ρ) → (⟦ B ⟧ᶠ ρ)
⟦ A ∧∧ B ⟧ᶠ ρ = (⟦ A ⟧ᶠ ρ) ∧ (⟦ B ⟧ᶠ ρ)
⟦ ⊤⊤ ⟧ᶠ ρ = ⊤
⟦_⟧ᶜ : Con → Env → Prop
⟦ [] ⟧ᶜ ρ = ⊤
⟦ A ∷ Γ ⟧ᶜ ρ = (⟦ A ⟧ᶠ ρ) ∧ (⟦ Γ ⟧ᶜ ρ)
⟦_⟧ᵈ : Γ ⊢ A → {ρ : Env} → ⟦ Γ ⟧ᶜ ρ → ⟦ A ⟧ᶠ ρ
⟦_⟧ᵈ {x ∷ Γ} (zero zero∈) p = proj₁ p
⟦_⟧ᵈ {x ∷ Γ} (zero (next∈ h)) p = ⟦ zero h ⟧ᵈ (proj₂ p)
⟦ lam th ⟧ᵈ = λ pₐ p₀ → ⟦ th ⟧ᵈ ⟨ p₀ , pₐ ⟩
⟦ app th₁ th₂ ⟧ᵈ = λ p → ⟦ th₁ ⟧ᵈ p (⟦ th₂ ⟧ᵈ p)
⟦ andi hf hg ⟧ᵈ = λ p → ⟨ ⟦ hf ⟧ᵈ p , ⟦ hg ⟧ᵈ p ⟩
⟦ ande₁ hfg ⟧ᵈ = λ p → proj₁ (⟦ hfg ⟧ᵈ p)
⟦ ande₂ hfg ⟧ᵈ = λ p → proj₂ (⟦ hfg ⟧ᵈ p)
⟦ true ⟧ᵈ ρ = tt
{--- Combinatory Logic ---}
data ⊢sk : Form → Prop where
SS : ⊢sk ((A ⇒ B ⇒ C) ⇒ (A ⇒ B) ⇒ A ⇒ C)
KK : ⊢sk (A ⇒ B ⇒ A)
ANDi : ⊢sk (A ⇒ B ⇒ (A ∧∧ B))
ANDe₁ : ⊢sk ((A ∧∧ B) ⇒ A)
ANDe₂ : ⊢sk ((A ∧∧ B) ⇒ B)
app : ⊢sk (A ⇒ B) → ⊢sk A → ⊢sk B
true : ⊢sk ⊤⊤
data _⊢skC_ : Con → Form → Prop where
zero : A ∈ Γ → Γ ⊢skC A
SS : Γ ⊢skC ((A ⇒ B ⇒ C) ⇒ (A ⇒ B) ⇒ A ⇒ C)
KK : Γ ⊢skC (A ⇒ B ⇒ A)
ANDi : Γ ⊢skC (A ⇒ B ⇒ (A ∧∧ B))
ANDe₁ : Γ ⊢skC ((A ∧∧ B) ⇒ A)
ANDe₂ : Γ ⊢skC ((A ∧∧ B) ⇒ B)
app : Γ ⊢skC (A ⇒ B) → Γ ⊢skC A → Γ ⊢skC B
true : Γ ⊢skC ⊤⊤
-- combinatory gives the same proofs as classic
⊢⇔⊢sk : ([] ⊢ A) ⇔ ⊢sk A
⊢sk→⊢ : ⊢sk A → ([] ⊢ A)
⊢sk→⊢ SS = lam (lam (lam ( app (app (zero $ next∈ $ next∈ zero∈) (zero zero∈)) (app (zero $ next∈ $ zero∈) (zero zero∈)))))
⊢sk→⊢ KK = lam (lam (zero $ next∈ $ zero∈))
⊢sk→⊢ ANDi = lam (lam (andi (zero $ next∈ $ zero∈) (zero zero∈)))
⊢sk→⊢ ANDe₁ = lam (ande₁ (zero zero∈))
⊢sk→⊢ ANDe₂ = lam (ande₂ (zero zero∈))
⊢sk→⊢ (app x x₁) = app (⊢sk→⊢ x) (⊢sk→⊢ x₁)
⊢sk→⊢ true = true
skC→sk : [] ⊢skC A → ⊢sk A
skC→sk SS = SS
skC→sk KK = KK
skC→sk ANDi = ANDi
skC→sk ANDe₁ = ANDe₁
skC→sk ANDe₂ = ANDe₂
skC→sk (app d e) = app (skC→sk d) (skC→sk e)
skC→sk true = true
lam-sk : (A ∷ Γ) ⊢skC B → Γ ⊢skC (A ⇒ B)
lam-sk-zero : Γ ⊢skC (A ⇒ A)
lam-sk-zero {A = A} = app (app SS KK) (KK {B = A})
lam-sk (zero zero∈) = lam-sk-zero
lam-sk (zero (next∈ h)) = app KK (zero h)
lam-sk SS = app KK SS
lam-sk KK = app KK KK
lam-sk ANDi = app KK (app (app SS (app (app SS (app KK SS)) (app (app SS (app KK KK)) (app (app SS (app KK ANDi)) (lam-sk-zero))))) (app KK lam-sk-zero))
lam-sk ANDe₁ = app KK (app (app SS (app KK ANDe₁)) lam-sk-zero)
lam-sk ANDe₂ = app KK (app (app SS (app KK ANDe₂)) lam-sk-zero)
lam-sk (app x₁ x₂) = app (app SS (lam-sk x₁)) (lam-sk x₂)
lam-sk true = app KK true
⊢→⊢skC : Γ ⊢ A → Γ ⊢skC A
⊢→⊢skC (zero h) = zero h
⊢→⊢skC (lam x) = lam-sk (⊢→⊢skC x)
⊢→⊢skC (app x x₁) = app (⊢→⊢skC x) (⊢→⊢skC x₁)
⊢→⊢skC (andi x y) = app (app ANDi (⊢→⊢skC x)) (⊢→⊢skC y)
⊢→⊢skC (ande₁ x) = app ANDe₁ (⊢→⊢skC x)
⊢→⊢skC (ande₂ x) = app ANDe₂ (⊢→⊢skC x)
⊢→⊢skC (true) = true
⊢⇔⊢sk = ⟨ (λ x → skC→sk (⊢→⊢skC x)) , ⊢sk→⊢ ⟩